High‐latitude intermittent ionospheric scintillations: Exploring the Castaing distribution. Issue 8 (13th August 2015) - Mezaoui, H.; Hamza, A. M.; Jayachandran, P. T.
Abstract We present a multiscale analysis of the received amplitude fluctuations of the L1 GPS signal. The analysis consists of constructing a differential amplitude signal by taking the difference between the signal at time t and the signal at time t + τ, where τ represents a time lag. The probability density functions of the measured differential amplitude fluctuations are computed and fitted with Castaing distributions. The fourth normalized moment of the distributions is used to investigate the intermittent nature of the signal. The results reveal direct evidence that the intermittent aspect of the investigated scintillation events is more pronounced at small differential time lags than at long ones.